Pedagang Tradisional Sebagai Pelaku UMKM Mitra Usaha BMT Walisongo dalam Pembiayaan Produktif - Mawadah, Sokhikhatul (BISNIS, 2019)
The purpose of this study is to analyze how the role of BMT Walisongo is a provider of productive financing as a business partner for traditional merchant MSME in the Mijen market in terms of capital. Average traditional traders from the middle to lower classes, so they have not been able to overcome the problems of the needed capital. On the other hand the role of BMT in providing productive financing has very good potential for economic development, especially in the development of jobs for small and medium-sized communities, so as to be able to provide benefits that can be felt by the surrounding community. This study using descriptive qualitative methods by studying two sources, namely primary data and secondary data.